Cellulose-based molecularly imprinted red-blood-cell-like microparticles for the selective capture of cortisol. (1st August 2018) - Hayashi, Koichiro; Hayashi, Hikaru; Yamada, Shota; Sakamoto, Wataru; Yogo, Toshinobu
Graphical abstract: Highlights: Molecularly imprinted red-blood-cell-like microparticle with magnetic nanoparticles. Deformable MI-M-RBC-MPs passing through pores less than their diameter. Selective capture of cortisol from a solution containing various similar molecules. Collection of flowing MI-M-RBC-MPs using magnets. Abstract: Magnetite-nanoparticle-containing red-blood-cell-like-microparticles (M-RBC-MPs) with a selective ability for trapping cortisol (COR) were synthesized by an electrospray technique of a molecularly imprinted ethyl(hydroxyethyl) cellulose (EHEC)-based precursor. The as-synthezied M-RBC-MPs were ∼3-μm-disks with a dent. M-RBC-MPs contained magnetite nanoparticles below 15 nm in diameter, which exhibited magnetization and no room-temperature coercivity. The molecularly imprinted M-RBC-MPs (MI-M-RBC-MPs) passed through pores less than their diameter. The MI-M-RBC-MPs selectively trapped COR from a solution containing molecules similar to COR, whereas non-imprinted M-RBC-MPs did not trap COR. Furthermore, magnets were used to capture the water-dispersed MI-M-RBC-MPs flowing in a tube. Based on the above results, MI-M-RBC-MPs may selectively trap COR while simultaneously circulating in the blood, followed by their removal from the blood using magnets.